BIOMOLECULAR SKILL ENHANCEMENT PROGRAM FOR LABORATORY STAFFERS OF POLITANI KUPANG IN SUPPORTING AGRICULTURAL-RELATED LAB PRACTICES AND RESEARCHES - Stormy Vertygo (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2020)
As one of the prominent vocational institution in East Nusa Tenggara (NTT), State Agricultural Polytechnic of Kupang (Politani Kupang) strive to create graduates not only with field skills but also sufficient skills in the laboratory. In fact, most of the laboratories in the institution are very well equipped with high and vast technologies of the latest innovations, especially for molecular-level analysis. However, much is still unknown from the lab staffers on the procedures to operate it. Unfortunately, this would in turn hinder the assistance in academic activities such as lab practices, sample analysis and researches related to Agricultural field. In order to not make all these equipment and facilities wasteful, Politani Kupang in coordination with Forum Academia NTT (FAN) and Institute of Resource Governance and Social Change (IRGSC) Kupang initiate the program to enhance the skills of Politani Kupang lab staffers in Biomolecular field. This training was conducted from 15th to 20th of June 2020 in the Laboratory of Agricultural Biotechnology under the major of Crop & Horticulture Plants. By the end of the program, it could be concluded that the lab staffers have now known the basic procedures to operate/run lab apparatuses/methods such as: RNA isolation, Electrophoresis, UV Gel-doc, PCR and qPCR machines.Keywords: Biomolecular skills, Agricultural-related, Enhancement, Lab staffers, Politani Kupang